A presença da linguagem plástica na ação clínica: diálogos com a perspectiva fenomenólogica existencial - Silva, Mércia Gomes da (2015)
This study starts from questions originated by the author s experience as a psychologist in different clinical contexts, in which the plastic expression was used. The study aims to understand how the presence of the plastic language works on the clinical action under an existential phenomenological perspective, to present the presence of the plastic language in different clinical practices and discuss the clinical psychology action under an existential phenomenological perspective. The phenomenal basis is given by the researcher s experience and by clinical psychologists who accept to participate as interlocutors. The narratives collection procedure happened through interviews/testimonials, that allowed the exchange of experiences regarding the clinical practices of the participants and through a field report where the author/ researcher s experiences were registered.Through this context it is possible to go along different senses outlined in different clinical practices modalities developed by the four interlocutors. Aiming to offer psychological support for those who look toward (re)thinking about care and the way they lead their existences. The approaching and interpretation of the experiences, inspired on the analytics sense developed by Dulce Critelli points how plastic language can assume a position of presence and interlacement with the clinical work, so that, presenting and happening in a so interspersed way, is not possible to reduce to a logic of mere use or technical application. On this direction, plastic language is reflected as being closer to a poetic and gestural dimension, once that it runs away from causal and explicative relations as language has been daily molded in our times. Considerations are set concerning an understanding that clinical action in an errant movement and senses building contributes for the people to imply and care about their existences starting from the experience s expansion they make with their own language. This perspective is linked to a notion that considers the intimal relation among being, feeling, thinking and acting in the world. This way, understand the clinical action as an opportunity of listening and embracement to ethical, esthetic/sensible and poetical dimensions that composes existence. Giving value to the client/user/group s comprehensive horizon so they can appropriate the way they are connected to the world.